Life-Span Extension From Hypoxia in Caenorhabditis elegans Requires Both HIF-1 and DAF-16 and Is Antagonized by SKN-1 - Leiser, Scott F. (Oxford University Press, 2013)
Stabilization of the hypoxia-inducible factor (HIF-1) protein extends longevity in Caenorhabditis elegans. However, stabilization of mammalian HIF-1α has been implicated in tumor growth and cancer development. Consequently, for the hypoxic response to benefit mammalian health, we must determine the components of the response that contribute to longevity, and separate them from those that cause harm in mammals. Here, we subject adult worms to low oxygen environments. We find that growth in hypoxia increases longevity in wild-type worms but not in animals lacking HIF-1 or DAF-16. Conversely, hypoxia shortens life span in combination with overexpression of the antioxidant stress response protein SKN-1. When combined with mutations in other longevity pathways or dietary restriction, hypoxia extends life span but to varying extents. Collectively, our results show that hypoxia modulates longevity in a complex manner, likely involving components in addition to HIF-1.